Análise espaço-temporal da mortalidade infantil em uma capital do sudeste brasileiro: um olhar para as diferenças intraurbanas - Jáder Pereira Almeida (2024)
Infant mortality rate (IMR) is a measure of the health status of a community/population. Despite observing a reduction in this indicator over the years, both in developed and developing countries, infant mortality remains a significant challenge in the field of Public Health, especially for vulnerable populations. In addition, there are few Brazilian studies that assess intraurban differences in IMR within large cities. In the city of Belo Horizonte, Minas Gerais, researchers have emphasized the need to better understand the social determinants related to place of residence and their impact on the quality of child and adolescent health, specifically in slums and favelas. Main Objective:Assess the spatiotemporal evolution of infant deaths in a southeastern Brazilian capital according to different places of residence. Methods: Ecological study with descriptive and analytical analysis of infant mortality in the city of Belo Horizonte, between the years 2002 and 2020. The main outcome was the infant mortality rate, and secondary outcomes were early neonatal, late neonatal, and post-neonatal mortality rates. The main independent variable was the place of residence (slums versus formal city). Other covariates used were the health vulnerability index, race, and maternal age at the time of infant death. The outcomes were visualized through trend graphs, considering three areas: the slums, the formal city, and the city of Belo Horizonte. Additionally, an association analysis was conducted using the Negative Binomial Regression model. Results: A total of 6,343 infant deaths and 573,040 live births were georeferenced between 2002 and 2020. There was an overall reduction in the infant mortality rate in the city of Belo Horizonte by 30% over the analyzed period. Infant mortality curves in slums and favelas were above the historical average of the city of Belo Horizonte and the formal city, showing an initial downward trend but with an apparent upward pattern mainly from 2014 onwards. Most deaths were of children classified as non-white, and the average maternal age at the time of infant death increased over the analyzed period. In the association analyses, slum areas showed an infant mortality rate 20% higher than the formal city (RR = 1.2; 95% CI 1.1–1.3). Among the secondary outcomes, the early neonatal mortality rate stood out for the smallest annual reduction (RR = 0.98; 95% CI 0.97–0.99), while post-neonatal mortality was the component with the highest relative risk in the slums (RR = 1.38; 95% CI 1.18–1.60). Conclusion: Despite the reduction in infant mortality rates in recent years in the city of Belo Horizonte, the results indicate worse indicators in the slums compared to the formal city, particularly in the post-neonatal component, suggesting the existence of intra-urban health inequalities linked to place of residence. Therefore, greater government investments are needed in socially vulnerable regions in Belo Horizonte, ensuring access to quality care and respecting the principle of equity of the Unified Health System.